2010
DOI: 10.1016/j.neuroscience.2010.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Brain connectivity in positive and negative syndrome schizophrenia

Abstract: If, as is widely believed, schizophrenia is characterised by abnormalities of brain functional connectivity, then it seems reasonable to expect that different subtypes of schizophrenia could be discriminated in the same way. However, evidence for differences in functional connectivity between the subtypes of schizophrenia is largely lacking and, where it exists, it could be accounted for by clinical differences between the patients (e.g. medication) or by the limitations of the measures used. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…Such matrices arise frequently, e.g., in EEG studies for brain connectivity [26] and synthetic aperture radar research [12]. We assume K p, since then S has full rank p, and S is positive definite, with probability one.…”
Section: A Complex Wishart Matricesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such matrices arise frequently, e.g., in EEG studies for brain connectivity [26] and synthetic aperture radar research [12]. We assume K p, since then S has full rank p, and S is positive definite, with probability one.…”
Section: A Complex Wishart Matricesmentioning
confidence: 99%
“…The choices for p and K are applicable to the neuroscience studies [25], [26] mentioned in the Introduction; likewise the range of N considered. The same is true of these parameter choices in the further simulations to follow.…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing number of independent brain processes, decreases of EEG coherence are to be expected. Several studies on scalp EEG connectivity in schizophrenia indeed reported decreased EEG coherence (e.g., Flor-Henry and Koles, 1984; Merrin and Floyd, 1992; Tauscher et al, 1998; Winterer et al, 2001), but others reported increases (e.g., Ford et al, 1986; Nagase et al, 1992; Mann et al, 1997; Wada et al, 1998) or increases as well as decreases depending on patients' subtype or medication (Knott et al, 2002; Medkour et al, 2010). Some coherence studies analyzed no-task resting, others task conditions, contributing to the differences in results.…”
Section: Introductionmentioning
confidence: 99%
“…Strictly speaking, instead of describing the FCG similarity (Garces et al, 2016) intuitively, the RE can only detect the global difference between the two matrices. To further evaluate the quantized similarity between FCGs, this study exploited HD as another metric to differentiate the two graphs via the transformed times (Makram Talih, 2005; Medkour et al, 2010; van Wijk et al, 2010; Garces et al, 2016). …”
Section: Introductionmentioning
confidence: 99%